Roteiro interativo: processo de construção de um documentário sobre o maestro Forró. - Guedes, Alessandro de Farias (2021)
Interactive narratives are increasingly present in the contemporaneity of hyperconnected societies. This work focuses on interactive narratives related to cinema, in particular the documentary for the realization of a script for an interactive documentary. The research starts from the conceptual and theoretical aspects about the audiovisual and its transformations. In general, the contributions on Interactive Narrative by Primo (2003) and Cirino (2012), Non-fiction Cinema by Nichols (2008) and Bezerra (2019), Interactive Documentary by Manovich (2001) and Winston, Vanstone; Chi (2012), plus investigations on the script by Comparato (2000) and Renó (2011). After the theoretical conceptualizations, the work goes to the elaboration of the script, following the Rhizomatic Circular Algorithm Flowchart Model, created by Denis Renó (2011). For the script proposed in this research, the character Maestro Forró and Orquestra Popular da Bomba do Hemetério was chosen, who have in their work the premises of “research, maintenance, reinterpretation and interaction”. These premises serve as a unifying element of the fragments (micro-stories) of the script for an interactive documentary.